Eksplorasi Pembelajaran Matematika Berbasis Etnomatematika Melalui Objek Wisata Kolam Renang Kuala Mega - Ayu Trisiya, Kapita; Andhany, Ella (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research was conducted to find elements of mathematics (ethnomathematics) in the swimming pool tourist attraction in Tanjung Morawa, Indonesia. This research uses qualitative methods with an ethnographic approach. The data used is data obtained from literature studies, observations, documentation and interviews. Observation and documentation are used to identify ethnomathematics at the Kuala Mega Swimming Pool tourist attraction. Meanwhile, literature and interviews were used to find out more about the architectural artistic values in Kuala Mega buildings. The results of this research are that there are elements of mathematics (ethnomathematics) in the Kuala Mega tourist attraction, namely the concepts of rectangles, circles, octagons and parallel lines. Through the activity of observing the Kuala Mega building in mathematics learning, the ethnomathematics approach explains that cultural elements can be used in mathematics learning.